2007
DOI: 10.1145/1243987.1243988
|View full text |Cite
|
Sign up to set email alerts
|

Test conditions for fault classes in Boolean specifications

Abstract: Fault-based testing of software checks the software implementation for a set of faults. Two previous papers on fault-based testing [Kuhn 1999;Tsuchiya and Kikuno 2002] represent the required behavior of the software as a Boolean specification represented in Disjunctive Normal Form (DNF) and then show that faults may be organized in a hierarchy. This article extends these results by identifying necessary and sufficient conditions for fault-based testing. Unlike previous solutions, the formal analysis used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…The following formula can be designated intuitively to compute the priorities: (27) This formula fulfills the requirement of Definition 8 that p i and Inf i are inversely proportional and the priority for input i also represents the contribution of concerning influence to the total influence. Applying Formula (27), the test pairs can be assigned the priorities as shown below: Below, the effect of the proposed prioritization method will be demonstrated using only one fault hypothesis, ORF for the sake of simplicity. According to ORF, there exist three mutants of expression f as given below: that belong to two different decisions, e.g.…”
Section: Definition 8 (Spectral Test Prioritization) Let F (X)mentioning
confidence: 99%
“…The following formula can be designated intuitively to compute the priorities: (27) This formula fulfills the requirement of Definition 8 that p i and Inf i are inversely proportional and the priority for input i also represents the contribution of concerning influence to the total influence. Applying Formula (27), the test pairs can be assigned the priorities as shown below: Below, the effect of the proposed prioritization method will be demonstrated using only one fault hypothesis, ORF for the sake of simplicity. According to ORF, there exist three mutants of expression f as given below: that belong to two different decisions, e.g.…”
Section: Definition 8 (Spectral Test Prioritization) Let F (X)mentioning
confidence: 99%
“…Figure 4 shows one IRF of the cause-effect graph in Figure 3 where C1 is replaced by C4. IRF is similar to the fault class, referred to as Variable Reference Fault (VRF) in the fault model for Boolean expressions [3,7,12]. IRF and VRF differ in a way of dealing with a nonsingular expression which contains multiple occurrences of a Boolean variable.…”
Section: B Fault Model Includesmentioning
confidence: 99%
“…The described typical programming errors involve missing or extra literals/variables, and the use of incorrect operators and operands. Some researchers have recently introduced ten fault types for general Boolean expressions, including ENF, SA0, SA1, VNF, ASF, ORF, VRF, MVF, CCD, and CDF [24,10]. However, these terminologies are a bit confusing.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…The value range for the fault-detection ratios on LIF is from 34.45% to 100%, just marginally higher than that of LOF (from 31.6% to 98.51%). Kapoor and Bowen [24] conjectured that ENF might be the weakest one among eight fault types for general Boolean expressions; in other words, the detection of any other fault type can also guarantee the detection of ENF. Though this conjecture has been proven wrong by Chen et al [10], our observation with respect to ENF demonstrated that ENF at least can be revealed very easily as compared with other fault types.…”
Section: Rq1: Fault-detection Effectivenessmentioning
confidence: 99%